PENGATURAN PIDANA MATI DALAM UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PERMBERANTASAN TINDAK PIDANA KORUPSI DIHUBUNGKAN DENGAN HAK ASASI MANUSIA - Yani, Rinda; Effendi, Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Corruption everyone who categorized against the law, committing to enrich themselves, enriching himself or another person or corporation. To combat corruption the government sets the maximum penalties in the form of the death penalty sentence. But in reality sentenced to the death penalty is never applied to the perpetrators of corruption. The purpose of this thesis, namely: first, to know the Criminal Dead regulated in Law Number 20 of 2001 on the Amendment of Law No. 31 of 1999 on Corruption Eradication associated with human rights, second, to determine the settings death penalty connected with the purpose of punishment.This type of research can be classified into types of normative juridical research. Source of data used were obtained through three (3) legal materials, namely: primary legal materials, secondary and tertiary. The data collection techniques were done with literature.From the results of research and discussion, there are two main things that can be inferred. Firstly, Criminal dead regulated in Law Number 20 of 2001 on the Amendment of Law No. 31 of 1999 on Corruption Eradication linked to Human Rights, that the regulation of capital punishment stipulated in Law No. 20 of 2001 Amendment OF No. 31 of 1999 because the Corruption is an extraordinary crime (extraordinary crime). Moreover, corruption is not only detrimental to the state finance but also harm society. If seen by the view of Human Rights Implementation of the death penalty for criminals, not a human rights violation. Secondly, setting capital punishment is linked to the aims of punishment can provide recompense to the perpetrator of the crime of corruption does. Besides the death penalty relationship with the purpose of punishment capable of improving public discontent as a result of the crime of corruption and the law Maintaining order in society and improve peoples lives due to such corruption. First authors suggestion, setting the death penalty in Act No. 20 of 2001 Amendment Act No. 31 of 1999 needs to be maintained because it basically does not violate human rights. Second, the purpose of punishment relationship with the death penalty should be the basis of a benchmark to improve the rules of law and peoples lives.Keywords: Criminal Setting Off-Corruption-Human Rights